1992
DOI: 10.1159/000204595
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Hemolytic Anemia Presenting in Sézary Syndrome

Abstract: A 52-year-old man, who presented with Sézary syndrome with autoimmune hemolytic anemia (AIHA) and was successfully treated with corticosteroids is reported. Helper function assay determining immunoglobulin confirmed inducer capability of this clonal population. This patient brings to 4 the number of cases of T cell cutaneous lymphoma and AIHA now reported in the English literature, and is the first case of Sézary syndrome and AIHA thus far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…While the bone marrow biopsy did reveal advanced disease, the patient had an elevated reticulocyte count, demonstrating capacity for bone marrow production. Autoimmune hemolytic anemia was also a consideration and has been previously reported in patients with SS [ 8 ]. In this case, the patient’s DAT was negative.…”
Section: Discussionmentioning
confidence: 99%
“…While the bone marrow biopsy did reveal advanced disease, the patient had an elevated reticulocyte count, demonstrating capacity for bone marrow production. Autoimmune hemolytic anemia was also a consideration and has been previously reported in patients with SS [ 8 ]. In this case, the patient’s DAT was negative.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the case reported by Evers et al [1] as we have recently reported a 47-year-old white woman with the diagnosis of cu taneous T cell lymphoma (T4, N3, M0, Bu), who suffered a hemolytic crisis (hemoglobin 3.5 g/dl) due to a widespccificity IgG autoantibody of sus pected anti-D specificity [2]. We thor oughly reviewed the literature, and although Padavic-Knox et al [3] stated that there were two previous reports of autoimmune hemolytic anemia and cutaneous T cell lym phoma, referring to White et al [4] and Lawrence et al [5], they did not realize he was the same patient.…”
Section: Autoimmune Hemolytic Anemia and Cutaneous T Cell Lymphoma: Rmentioning
confidence: 92%
“…We thor oughly reviewed the literature, and although Padavic-Knox et al [3] stated that there were two previous reports of autoimmune hemolytic anemia and cutaneous T cell lym phoma, referring to White et al [4] and Lawrence et al [5], they did not realize he was the same patient. Ap parently, Evers et al [1] were unaware of this fact as well. For this reason, the case reported by us [1] constitutes the third case of autoimmune hemolytic anemia in a patient with cutaneous T cell lymphoma.…”
Section: Autoimmune Hemolytic Anemia and Cutaneous T Cell Lymphoma: Rmentioning
confidence: 99%
See 1 more Smart Citation